The Neotropical genus Ginungagapus gen. nov. (Hesperiidae, Hesperiinae, Moncini): phylogenetic position and taxonomic review - Carneiro, Eduardo; Mielke, Olaf H. H.; Casagrande, M. M. (Zootaxa, 2015)
A taxonomic and phylogenetic study based on morphological characters revealed the type species of the genus Lucida Evans, 1955, Lucida lucia (Capronnier, 1874) to be paraphyletic to other species of the genus. As a result, a new genus, Ginungagapus gen. nov., is erected including four species previously placed in Lucida: Ginungagapus schmithi (Bell, 1930) comb. nov., Ginungagapus bocus (Bell, 1947) comb. nov., Ginungagapus ranesus (Schaus, 1902) comb. nov., and Ginungagapus rogan (Evans, 1955) comb. nov.; and four new species are added: Ginungagapus awarreni, sp. nov., Ginungagapus tangerinii, sp. nov., Ginungagapus fiedleri, sp. nov. and Ginungagapus brasilia, sp. nov. The new genus is taxonomically revised, genitalia are illustrated, except of the female of G. rogan (Evans, 1955) and of the male of G. brasilia, sp. nov., which are still unknown. An identification key is provided.